DIETARY COMPLIANCE AND GLYCEMIC MONITORING STATUS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AT TRA VINH GENERAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Introduction:  Diabetes mellitus is a common non-infectious disease characterized by disorders of glucose metabolism and insulin resistance. The prevalence of diabetes mellitus has been rapidly increase in recent years.Objectives: To determine the rate of dietary compliance and glycemic monitoring status among patients with type 2 diabetes in the outpatient setting at Tra Vinh General Hospital.Methods: A descriptive cross-sectional study was conducted on 308 outpatients at Tra Vinh General Hospital from April 2025 to June 2025. Patients who met the inclusion criteria were selected and interviewed to collect complete information using a questionnaire form.Results: The prevalence of comorbidities was 87.3%, with hypertension being the most common comorbid condition (90.3%). Most patients were treated primarily with oral medications (79.2%). Overall treatment dietary compliance (79.5%) and compliance with blood glucose monitoring and periodic health check-ups (12.3%).Conclusion: Type 2 diabetes is emerging as an urgent public health challenge. The findings of this study may support the development and implementation of appropriate management strategies.
Keywords: Type 2 diabetes mellitus, dietary compliance, glycemic monitoring